Spatio-Temporal Techniques for Anti-Jamming in Embedded Wireless Networks. (29th March 2010) - Pajic Pajic, Miroslav Miroslav; Mangharam Mangharam, Rahul Rahul
Abstract : Electromagnetic jamming results in a loss of link reliability, increased energy consumption and packet delays. In the context of energy-constrained wireless networks, nodes are scheduled to maximize the common sleep duration and coordinate communication to extend their battery life. This coordination results in statistical and predictable activity patterns that may be easily detected and jammed. To eliminate spatio-temporal patterns of communication in the link and network layers, we present WisperNet, an energy-efficient anti-jamming protocol. WisperNet employs hardware-based time synchronization and lightweight cryptographic hashing for coordinated temporal randomization of slot schedules at the link layer and adapts routes to avoid static jammers in the network layer. We demonstrate that WisperNet reduces the efficiency of any statistical jammer to that of a random jammer, which has the lowest censorship-to-link utilization ratio. In the presence of a statistical jammer, WisperNet provides sub-2% packet drop ratios for link utilization up to 50%. In addition, the jammer's censorship efficiency is linear with link utilization as it is unable to extract any communication patterns. WisperNet is more efficient than low-power CSMA protocols in terms of energy, effective network throughput, reliability and delay.